Performance analysis of DCO OFDM and DCO WOFDM systems in MMF optical links - Mirbadin, Anoush (2011)
Orthogonal Frequency Division Multiplexing (OFDM) is a Multi Carrier Modulation (MCM) technique which has been known as a powerful tool to overcome Inter Symbol Interference (ISI) caused by a dispersive channel. Since optical communication channels are dispersive environments, during last decades optical OFDM has been proposed for compensating modal and chromatic dispersion in the optical communication systems. The purpose of this study is to analyze and compare the performances of DC biased Optical Orthogonal Frequency Division Multiplexing (DCO OFDM) and DC biased Optical Wavelet based Orthogonal Frequency Division Multiplexing (DCO WOFDM) systems in Multi Mode Fiber (MMF) optical links. Mach Zehnder Modulator (MZM) was utilized as the optical modulator. The simulations were carried out using Optisystem software. Bit Error Rate (BER) versus transmission distance curves as well as Optical Signal to Noise Ratio (OSNR) versus transmission distance curves were used as criterions for evaluating the performances of the simulated systems. Simulation results show that DCO WOFDM system offers considerable improvement in BER performance compared to DCO OFDM system. It was found that error free transmission distance for DCO OFDM and DCO WOFDM occurred at 330 m and 360 m, respectively. The achieved BER by DCO WOFDM at a 375 m link distance is 23 times smaller than the achieved BER by DCO OFDM at the same link distance. Even though, the bandwidth of DCO WOFDM signal is twice the bandwidth of DCO OFDM signal. Sensitivity of DCO WOFDM signal to noise is slightly better than the sensitivity of DCO OFDM signal to noise. These benefits are due to the fact that the Power Spectral Density (PSD) of DCO WOFDM signal is more compatible with the channel frequency response in contrast to the PSD of DCO OFDM signal.